PROPOSED ORGANIZATIONAL STRUCTURE FOR AGRICULTURAL INITIATIVE MEDIA IN IRAQ - & Naji, AL-Hamadani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The current paper aims at building  Proposed Organizational Structure For Agricultural Initiative  Media in Iraq for observing the opinions of  the employees working in the Agricultural initiative  and those working in  the media and agricultural sector on three levels as to measure suitability of  Proposed informational  Organizational Structure . In order to carry out goals of the research, a questionnaire has been prepared andincluded fifth scale consisting of 115 items distributed on 6 space and 22 axils. The research has been carried out on cluster random sample with 50% of all offirst. Iraqi governorates of southern, middle and northern (15) except Kurdistan governorates, withKirkuk governorate assign for the north (the area of the research) while Baghdad, Diyala, Karbala, Al-Najaf for the middle, and Basra,Maysan and The Qar for the south. Seconed.employees agriculturedistributedon three levels, the first level  includes  the  supreme committee of  agriculture initiative in  the center  and branch committees  in the governorates, the second level includes informational department employees in directorates of agriculture and informational sector in agricultural training and instructions , while the third level  includes agricultural employees  working in  the centers and agricultural departments .  Through having the scale of  informational  organizational  structure offered to the sample of  the research , it has finally reached  to items of building proposed organizational structure  by using  the following scale:  the item within  the finished form  for building the structure  has been obtained  a larger average  than the proposed average amounted  (3 degree) ; the result was to remain all items in the final form  for building  the proposed informational  organizational structure in all three levels  of the research sample. Then, it has been reached to build the finished form of the proposed informational organizational structure of agricultural initiative Media.  The researcher has recommended tonecessarily provide necessities to succeed this proposed informational organizational structure of agricultural initiative Media since being considered as a basic element for succeeding the High Committee of Agricultural Initiative.